THE POWER OF ENGLISH: RECOGNIZING AND UTILIZING THE TREMENDOUS IMPACT OF THE ENGLISH LANGUAGE ON THE COMMUNITY - Andi Kaharuddin (Universitas islam Negeri Alauddin Makassar, 2019)
This paper discusses two things i.e. the power of English as the most dominant language in the world and the concepts of using English and using the power of English. English today emerges as a power which can’t be defeated by any languages in the world. The domination of English is obviously seen from its status as: the most rapidly growing language, the most widely spoken language, the most popular content language on the internet, the most preferred language for the scientific communities, the number-one language for business, and the most preferred Language for publishing. Knowing this, learners of English should be proud since they evidently learn something extraordinary. The pride should be reflected in two things i.e. learning English earnestly to achieve benefits of having English skills and turning the achivement of benefits to providing benefits for the communities. However, the reality shows that many learners simply learn English to achieve benefits, for example, to get a job or to win a scholarship abroad. Meanwhile, few learners are aware of using English to bring benefits. As the learners learn English and finally achieve a benefit. This is called Using English. Yet, they learn English and achieve a benefit, and could bring benefits to the communities. This is called Using the Power of English. To use the power of English, we should have and integrate English skills, knowledge, experiences, education, as well as professionalism. Therefore, the orientation of learning English should not just end immediately after Using English, but it should continue to Using the power of the English.